Comparative analysis of story-grammar development: a cross-sectional study of Tamil-speaking child cochlear implant users and hearing peers in Tamil Nadu, India - Jenithaa Muthu; Krupa Venkatraman; Latika Ganesh (BMJ Open)
Objective This cross-sectional comparative study aimed to analyse and compare the story-grammar components in Tamil-speaking children with and without hearing impairment (HI) narratives.Design The study used a cross-sectional, comparative design to assess and compare narrative structures.Setting Data were collected at the Sri Ramachandra Institute of Higher Education and Research in Chennai, India.Participants 30 children participated in the study, including 15 children with severe to profound hearing loss who used cochlear implants and 15 with normal hearing. The participants were language-age-matched children aged 3–5 years, proficient in Tamil.Interventions No specific interventions were implemented in this study.Main outcome measures The primary outcome measures focused on story-grammar components, including settings, characters, initiating events, internal plans, attempts, outcomes, and resolution. These components were evaluated through narrative retellings by the children.Results Analysis of the narratives revealed significant differences between the two groups. Children with normal hearing demonstrated a higher representation of story-grammar elements than children with HI.Conclusions The findings suggest that children with normal hearing exhibit a more proficient understanding and utilisation of story structure in their story-telling than children with HI. This study highlights the importance of narrative analysis in language assessment, particularly for children with HI. Tailored interventions incorporating appropriate language stimulation techniques are needed to enhance children’s narrative skills with HI. Further research in this area is warranted.